Collecting crop genetic resources in the Mediterranean agricultural islands: Corsica (Part I-northern Corsica) - Bullitta, S.=700 1 Cifarelli, S.; Gladis, Th.; Hammer, K.; Laghetti, G.
(Es,Fr,En)
ilus., 5 ref.
Keywords: RECURSOS GENETICOS; CONSERVACION DE LOS RECURSOS; RECOLECCION; CULTIVOS; ITALIA